UAV assisted heterogeneous networks for public safety communications - Merwaday, Arvind; Guvenc, Ismail (2015 IEEE Wireless Communications and Networking Conference Workshops (WCNCW), 2015)
Communications play an important role during public safety operations. Since the current communication technologies heavily rely on the backbone network, the failure of base stations (BSs) due to natural disasters or malevolent attacks causes communication difficulties for public safety and emergency communications. Recently, the use of unmanned aerial vehicles (UAVs) such as quadcopters and unmanned gliders have gained attention in public safety communications. They can be used as unmanned aerial base stations (UABSs), which can be deployed rapidly as a part of the heterogeneous network architecture. However, due to their mobile characteristics, interference management in the network becomes very challenging. In this paper, we explore the use of UABSs for public safety communications during natural disasters, where part of the communication infrastructure becomes damaged and dysfunctional (e.g., as in the aftermath of the 2011 earthquake and tsunami in Japan). Through simulations, we analyze the throughput gains that can be obtained by exploiting the mobility feature of the UAVs. Our simulation results show that when there is loss of network infrastructure, the deployment of UABSs at optimized locations can improve the throughput coverage and the 5th percentile spectral efficiency of the network. Furthermore, the improvement is observed to be more significant with higher path-loss exponents.